Renal malakoplakia mimicking a malignancy and diagnosed by fine‐needle aspiration: A case report. Issue 11 (2nd May 2020) - Ho, Linh; Mehrotra, Sanjana
Abstract: Malakoplakia is a rare, granulomatous disease that affects a wide variety of organs and can have a clinical and radiographic presentation resembling that of malignancy. The genitourinary tract is the most commonly involved site. There are scant reported cases presenting as a locally advanced renal mass and even rarer, diagnosed by fine‐needle aspiration (FNA) cytology. We report clinical, imaging, cytologic, and histological findings of an interesting case of malakoplakia initially diagnosed by FNA cytology. We also briefly review the literature and emphasize the importance of recognizing this entity when encountered in an aspirate material, which can help mitigate the diagnostic confusion of malakoplakia for clinicians.